Accurate measurement of androgen after androgen esters: problems created by ex vivo esterase effects and LC‐MS/MS interference. (21st October 2018) - Ceponis, J.; Swerdloff, R.; Leung, A.; Hull, L.; Bai, F.; Longstreth, J.; Dudley, R.; Danoff, T.; Wang, C.
Abstract: Background: Ex vivo androgen prodrug conversion by blood esterases after oral androgen ester administration may result in an overestimation of the measured blood androgens. Objective: We investigated whether blood collection tubes with esterase inhibitors decreased the conversion of testosterone undecanoate (TU) and dimethandrolone undecanoate (DMAU) to their active metabolites, testosterone (T), and dimethandrolone (DMA), providing a more accurate assessment of circulating T/DMA levels. Methods: Blood was collected in tubes with/without esterase inhibitors from: (i) four healthy and four hypogonadal men receiving no androgens and spiked ex vivo with TU/DMAU; (ii) four men taking oral TU (Andriol ® ); and (iii) eight hypogonadal men dosed with oral 316 mg TU and 15 healthy men with 200 mg DMAU. T/DMA levels were measured by LC‐MS/MS. Results: Sodium fluoride (NaF, an esterase inhibitor) decreased measured T levels by 14.2% in men not receiving TU. Increasing amounts of TU/DMAU added to blood collected into plain tubes resulted in a concentration‐dependent overestimation of T/DMA that was reduced by collecting blood into NaF tubes (by 30–85%), and keeping samples at 4 °C and minimizing time prior to centrifugation. After oral TU/DMAU administration to men, when TU/DMAU levels were >15/10 ng/mL, respectively, blood collected in NaF tubes yielded lower measured T concentrations by 15–30% and DMA by 22% due to an additional inhibitory effect of NaF on blood esterases. Conclusion: NaF directly lowers plasma T/DMA levels measured by LC‐MS/MS and also inhibits blood esterase activity. Overestimation of T/DMA in blood collected in tubes without NaF after oral TU/DMAU administration is important for pharmacokinetics studies in drug development clinical trials but may have limited impact in clinical practice/utilization because the differences between measured and true androgen values are modest and the wide therapeutic androgen efficacy ranges obviate the need for highly accurate androgen measurements during therapy.